Long-term safety, tolerability, and efficacy of fremanezumab in migraine: A randomized study. (3rd November 2020) - Goadsby, Peter J.; Silberstein, Stephen D.; Yeung, Paul P.; Cohen, Joshua M.; Ning, Xiaoping; Yang, Ronghua; Dodick, David W.
Abstract : Objective: To assess the long-term safety, tolerability, and efficacy of fremanezumab, a fully humanized monoclonal antibody approved for the preventive treatment of migraine. Methods: A 52-week, multicenter, randomized, double-blind, parallel-group study evaluated fremanezumab monthly or quarterly in adults with chronic migraine (CM) or episodic migraine (EM). Safety and tolerability were assessed by adverse event (AE) monitoring (performed by the investigators), systematic local injection-site assessments (immediately and 1 hour after injection), laboratory/vitals assessments, and immunogenicity testing. Prespecified exploratory evaluations included change from baseline in the monthly number of migraine days, headache days of at least moderate severity, and days with any acute headache medication use. Change from baseline in headache-related disability (6-item Headache Impact Test scores) was also measured. Results: Of 1, 890 patients enrolled, 551 and 559 patients with CM received quarterly and monthly dosing; 394 and 386 patients with EM received quarterly or monthly, respectively. The most commonly reported AEs were injection-site reactions (induration 33%, pain 31%, and erythema 26%). Fremanezumab reduced monthly migraine days (CM quarterly −7.2 days, CM monthly −8.0 days, EM quarterly −5.2 days, EM monthly −5.1 days) and headache days of at least moderate severity (CM quarterly −6.4 days, CM monthly −6.8 days, EM quarterly −4.4, EM monthly −4.2 days) from baseline to 12 months. Reductions in any acute headache medication use and headache-related disability were also maintained over 12 months. Conclusions: Fremanezumab quarterly and fremanezumab monthly were well tolerated and demonstrated sustained improvements in monthly migraine days, headache days, and headache-related disability for up to 12 months in patients with migraine. ClinicalTrials.gov: NCT02638103. Classification of evidence: This study provides Class IV evidence that long-term fremanezumab treatment is safe, well tolerated, and effective at sustaining reductions in monthly migraine and headache days.